(untitled) (Res Gesta, 2022)
In the second half of the nineteenth century, the associative experience expanded throughout the Argentine territory with the arrival of European immigrants who sought, in this way, to respond to their needs and define their identity borders. In the city of Corrientes, in 1864 the Italian mutual aid association "Unione e Benevolenza" was founded. Disappeared after the Paraguayan War, the entity did not last in time. However, the arrival of Italians to the city continued and, in 1870, an association called "Unione e Fratellanza" was founded, and is still in activity today. Our objective is to analyze the process of integration of those Italian ethnic leaders into the traditional correntina elite. This integration was manifested by the insertion of peninsulars in political bodies of the city, by the marriage bonds they established and by the sociability practices they deployed.